A KAJIAN PENGEMBANGAN PEMBERDAYAAN UMKM HALAL YANG BERKELANJUTAN - Tania Alda; Fadylla Ramadhani; Chindy Elsana R; Ahmad Shalihin (Jurnal Manajemen Rekayasa dan Inovasi Bisnis, 2023)
Small and medium enterprises (SMEs) play an important role in most developing countries. In line with emerging markets, this is the right time for the empowerment of SMEs in the Halal Industry as it not only contributes to the growth of the national economy but most significantly is the way forward to create jobs for students who graduate from Halal knowledge. It was found that SMEs can develop, promote and maintain their business in the global halal market if the business excellence model can be adopted as a way to improve their SME business. Halal SMEs should be designed in line with the “business excellence concept” and “benchmark concept”. Halal-entrepreneurs must apply these concepts seriously in the business and market of the halal industry because the sector develops from time to time, especially in the Halal Food Industry, Pharmaceutical and Health Products, Halal Cosmetics, Halal Tourism and Travel, Halal Audit and Consulting